A special relationship : the United States and military government in Thailand, 1947-1958 - Fineman, Daniel, 1962- (Honolulu : University of Hawaii Press, 1997)
The development of the Thai-American alliance from 1947 to 1958 dramatically transformed both countries' involvement in Southeast Asia. Bounded by two important political events in Thailand, an army coup in 1947 and the military's assumption of complete control of government in 1958, the period witnessed both the entrenchment of authoritarian military government in Thailand and a revolution in U.S.-Thai relations. During these years the modern Thai political system emerged, and the United States established its interest and influence in mainland Southeast Asian affairs. The developments of the period made possible American's later, more extensive, involvement in Indochina. A Special Relationship provides the most comprehensive analysis of this critical founding period of the Thai-American alliance. It reveals surprising new information on joint covert operations in Indochina, American support for suppression of government opponents, and CIA involvement in Thai domestic politics.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- NOTE ON TRANSLITERATION AND THAI NAMES -- ABBREVIATIONS -- INTRODUCTION -- PART ONE: LEARNING TO LIVE WITH PHIBUN, 1947-1948 -- Chapter One. PRELUDE TO THE COUP, JANUARY 1947-NOVEMBER 1947 -- Chapter Two. KHUANG AND THE COUP, NOVEMBER 1947-APRIL 1948 -- Chapter Three. PHIBUN'S RETURN, APRIL-JUNE 1948 -- PART TWO: U.S. MILITARY AID AND THE TRANSFORMATION OF THAI FOREIGN POLICY, 1948-1950 -- Chapter four : Making the Case for Military Aid, April 1948-June 1949 -- Chapter Five. U.S. MILITARY AID AND THAILAND'S COMMITMENT TO THE WEST, JUNE 1949-DECEMBER 1950 -- PART THREE: FORMING THE ALLIANCE, 1950-1954 -- Chapter Six. THE ESTABLISHMENT OF AN AMERICAN MILITARY PRESENCE, JUNE 1950-DECEMBER 1951 -- Chapter Seven. THE UNITED STATES AND THE MILITARY'S CONSOLIDATION OF POWER, JUNE 1951-DECEMBER 1952 -- Chapter Eight. BUILDING THE BASTION, JANUARY 1953-SEPTEMBER 1954 -- PART FOUR: DEMOCRACY, DICTATORSHIP, AND THE NEW ALLIANCE, 1955-1958 -- Chapter Nine. DEMOCRATIZATION AND DETERIORATION, JANUARY 1955-SEPTEMBER 1957 -- Chapter Ten. DICTATORSHIP AND RESTORATION, SEPTEMBER 1957-DECEMBER 1958 -- CONCLUSION -- NOTES -- SELECTED BIBLIOGRAPHY -- INDEX -- About the Author.
Includes bibliographical references (pages 327-339) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Thailand -- Politics and government; Thailand -- Armed Forces -- Political activity; United States -- Foreign relations -- Thailand; Thailand -- Foreign relations -- United States; United States -- Military relations -- Thailand; Thailand -- Military relations -- United States; Thaïlande -- Politique et gouvernement; Thaïlande -- Forces armées -- Activité politique; États-Unis -- Relations extérieures -- Thaïlande.; Thaïlande -- Relations extérieures -- États-Unis.; États-Unis -- Relations militaires -- Thaïlande.; Thaïlande -- Relations militaires -- États-Unis.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; HISTORY -- Military -- United States; Armed Forces -- Political activity; Diplomatic relations; Military relations; Politics and government; Thailand; United States; Buitenlandse betrekkingen; Militaire samenwerking; Militaire regimes; 15.75 history of Asia; 15.85 history of America; Militärregierung; Außenpolitik; Thailand; USA; Thailand -- Politics and government; Thailand -- Armed Forces -- Political activity; United States -- Foreign relations -- Thailand; Thailand -- Foreign relations -- United States; United States -- Military relations -- Thailand; Thailand -- Military relations -- United States; Geschichte 1947-1958.; Geschichte -- 1947-1958; Thailand -- Armed Forces -- Political activity; Thailand -- Foreign relations -- United States; Thailand -- Military relations -- United States; Thailand -- Politics and government; United States -- Foreign relations -- Thailand; United States -- Military relations -- Thailand